2015
DOI: 10.1002/stem.2068
|View full text |Cite
|
Sign up to set email alerts
|

p38γ MAPK Is a Therapeutic Target for Triple-Negative Breast Cancer by Stimulation of Cancer Stem-Like Cell Expansion

Abstract: Triple-negative breast cancer (TNBC) is highly progressive and lacks established therapeutic targets. p38γ mitogen-activated protein kinase (MAPK) (gene name: MAPK12) is overexpressed in TNBC but how overexpressed p38γ contributes to TNBC remains unknown. Here we show that p38γ activation promotes TNBC development and progression by stimulating cancer stem-like cell (CSC) expansion and may serve as a novel therapeutic target. p38γ silencing in TNBC cells reduces mammosphere formation and decreases expression l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 52 publications
(135 reference statements)
0
46
0
Order By: Relevance
“…p38γ MAPK is activated through both overexpression and phosphorylation [3]. Asp to Ala mutation in the phosphorylation lip (D179) made p38γ MAPK constitutively active [14].…”
Section: Resultsmentioning
confidence: 99%
“…p38γ MAPK is activated through both overexpression and phosphorylation [3]. Asp to Ala mutation in the phosphorylation lip (D179) made p38γ MAPK constitutively active [14].…”
Section: Resultsmentioning
confidence: 99%
“…JNKs and p38 both possess oncogenic or tumor-suppressive functions [48]. In TNBC, both kinases are required for tumor development and progression, as mediated through cJUN/AP-1-activated signaling pathways [38, 49, 50]. Here, the decrease of JNKs and p38 activities in MB231 cells may destabilize cJUN/FRA1 or other cJUN/AP-1 complexes, leading to the transcriptional inactivation of genes involved in TNBC cell progression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown this pathway to be highly prevalent in TN breast cancer as opposed to other breast cancer subtypes (Hoeflich et al 2009; Balko et al 2012; Hashimoto et al 2014), thus supporting our findings. Studies have also shown that activation of MAPK pathway (Eralp et al 2008; Gholami et al 2014; Giltnane and Balko 2014; Hashimoto et al 2014; Qi et al 2015; Loi et al 2016) significantly correlates with tumor proliferation and disease progression in TN tumors. MAPK pathway is a sequentially activated cascade consisting of key genes such as Ras, Raf, MEK, and ERK.…”
Section: Discussionmentioning
confidence: 98%